2008
DOI: 10.1111/j.1743-6109.2008.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Erectile Dysfunction: Focus on NO Bioavailability and ROS Generation

Abstract: Introduction-Thirty million men in the United States suffer from erectile dysfunction (ED) and this number is expected to double by 2025. Considered a major public health problem, which seriously affects the quality of life of patients and their partners, ED becomes increasingly prevalent with age and chronic smoking is a major risk factor in the development of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 108 publications
3
73
0
5
Order By: Relevance
“…Ultimately, the NO causes a locally mediated increase in levels of the second messenger cGMP which further enhance the smooth muscle induced vasodilation. [11] If this NOS-NO-cGMP chain reaction cannot occur, it is defined as erectile dysfunction (ED), which is the inability to attain and/or maintain a satisfactory erection for sexual intercourse. Male sexual arousal is a complex process that involves the brain, hormones, nerves, muscles, psychological factors, the environment and blood vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the NO causes a locally mediated increase in levels of the second messenger cGMP which further enhance the smooth muscle induced vasodilation. [11] If this NOS-NO-cGMP chain reaction cannot occur, it is defined as erectile dysfunction (ED), which is the inability to attain and/or maintain a satisfactory erection for sexual intercourse. Male sexual arousal is a complex process that involves the brain, hormones, nerves, muscles, psychological factors, the environment and blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Moreover, ED can be viewed as an early marker of coronary endothelial dysfunction and atherosclerosis. [12,13] Risk factors such as diabetes mellitus, hypertension, smoking, hyperlipidemia, and a sedentary lifestyle are commonly seen in ED ( Figure 2) and ASCV diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention against smoking represents an important approach to reduce the risk of erectile dysfunction. 48 The Massachusetts Male Aging Study found that smokers are more prone to erectile dysfunction than non-smokers. 45 Another study showed that duration of smoking and the number of cigarettes smoked per day are directly correlated with erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…La DE es considerada un problema de salud pública mayor, que afecta seriamente la calidad de vida de los pacientes 29 , suele estar relacionada a importantes co-morbilidades como ECV, DM e HTA, que actúan, en ocasiones, exacerbándola. Basados en los hallazgos presentados en esta investigación y la literatura consultada puede concluirse que, tal como en otras poblaciones masculinas, la DE es un problema común entre hombres Latinoamericanos, con una prevalencia moderada que aumenta significativamente con la edad, y que es bastante alta en pacientes con antecedentes de ECV e indicación de rehabilitación cardíaca.…”
Section: Conclusiónunclassified